The lived experiences of mental health counselors who work with clients who experienced multilayered complex trauma: a hermeneutic phenomenology study. - Chiu, Lin (My University, 2026)
This hermeneutic phenomenological study explored the lived experiences of mental health counselors working with clients impacted by multilayered complex trauma, with a focus on counselor well-being, coping, and meaning-making. Although prior research has examined burnout, secondary traumatic stress, and vicarious trauma, limited qualitative work has explored how mental health counselors experience and sustain engagement in trauma work within complex and systemic contexts. Twelve licensed mental health counselors participated in semi-structured interviews. Data were analyzed using phenomenological reduction and interpretive analysis guided by the hermeneutic circle, resulting in approximately 1,100 significant statements organized into 25 meaning units and synthesized into six superordinate themes: bearing witness within systems, identity evolution from rescuer to companion, embodied impact, meaning-making and vicarious growth, coping and sustainable practice, and structural gaps and institutional strain. Findings suggest that trauma work is an embodied, relational, and systemically situated experience characterized by the co-occurrence of distress and growth. Mental health counselors described ongoing emotional and somatic impact alongside processes of identity development and meaning-making. Coping emerged as a multidimensional process supported by relational, embodied, and structural resources, with organizational contexts influencing mental health counselors’ ability to sustain engagement in trauma work. This study contributes to the counseling literature by conceptualizing counselor well-being as dynamic, relational, and shaped by interacting individual, relational, and systemic factors. Implications highlight the importance of somatic awareness, reflective supervision, and organizational support in promoting sustainable and ethical counseling practice.
Keywords: mental health counselor, complex trauma, vicarious trauma, vicarious growth, counselors wellbeing, hermeneutic phenomenology